Bilateral Thoracoabdominal Flaps Following Bilateral Mastectomy for Locally Advanced Breast Cancer - Ryohei Katsuragi, MD; Norie Abe, MD, PhD; Ayako Koki, MD; Hisamitsu Zaha, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Skin grafting is typically used to close large skin defects that may occur after mastectomy when the patient does not desire breast reconstruction. Herein, we present the case of a 49-year-old woman who underwent bilateral mastectomy for locally advanced breast cancer and had large skin defects on both sides of the chest that were closed using bilateral thoracoabdominal flaps. The flaps were designed in a hatchet shape to minimize the amount of flap dissection; after the flaps were elevated, indocyanine green angiography was performed to trim the areas with poor blood flow, and the wounds were closed without tension. The patient was discharged 9 days after surgery and completed postmastectomy radiation therapy. Six months after the surgery, the color and texture matched well, and no recurrence was observed. This is the first report demonstrating the effectiveness and safety of using bilateral thoracoabdominal flaps for bilateral mastectomy defects.